Effect of seed soaking and foliar spray of growth regulators on rice - Poornima Yadav P I (Department of Agronomy, College of Agriculture, 2001)
A field experiment was conducted at the Instructional Farm, College of Agriculture, Vellayani during the rabi 2000, to study the effect of seed soaking and foliar spray of growth and yield of rice. To assess the influence of different seed soaking chemicals on seed germination and seedling characters, a nursery study was conducted in CRD with four treatments and four replications (T1 –water soaking, T2 – soaking in Azospirillum, T3 – soaking in Penshibao, T4 – soaking in Azospirillum + Penshibao). The main field experiment was laid out in split split plot design with three replications. The treatments included four types of seed soaking (T1 – water soaking, T2 – soaking in Azospirillum, T3 – soaking in Penshibao, T4 – soaking in Azospirillum + Penshibao) in the main plots, five types of growth regulators as foliar spray (F1 – triacontanol, F2-GA3, F3-kinetin, F4-Penshibao and F5-water spray) in sub plots and two stages of application (S1-20 DAT and S2-20 and 30 DAT) in sub sub plots. Observations on nursey study revealed that soaking rice seeds in Azospirillum or Penshibao alone or in combination improved the germination percentage and all other seedling characters. Results of the main field experiment indicated that seed soaking, foliar spray, stages of application and their combinations had a significant influence on most of the growth characters, growth analysis parameters, yield attributing characters, yield, nutrient uptake and BCR. Soaking seeds in Penshibao + Azospirillum (T4), foliar spray with Penshibao (F4) and spraying at 20 and 30 DAT (S2) improved almost all growth characters, growth analysis parameters and chlorophyll content. These treatments also recorded the highest grain yield while straw yield was comparable for soaking in Penshibao alone and its combination with Azospririllum. Among the foliar sprays, Penshibao registered the highest grain and straw yield when applied at two stages compared to single application. In treatment combinations, soaking seeds in Azospirillum and Penshibao followed by foliar spray of Penshibao, soaking seeds in Penshibao followed by its foliar spray and soaking in Penshibao and Azospirillum followed by foliar spray of GA3 were found to be on par and significantly superior to other combinations. Nutrient uptake was also influenced by the three factors studied (seed soaking, foliar spray and stage of application). Nitrogen uptake was the highest for soaking seeds in Penshibao and Azospirillum and it was on par with soaking in Penshibao alone. Similarly foliar spray with Penshibao at 20 and 30 DAT registered the highest N uptake at harvest. The different chemicals used for seed soaking were found to have a comparable effect and superior to water soaking on P uptake. Among the combinations, soaking in Penshibao and Azospirillum with foliar spray of Penshibao at 20 and 30 DAT registered the highest values for N,P and K uptake. The economic analysis showed that the individual effect of combind soaking in Azospirillum (600 g ha-1) and Penshibao (100 ppm), foliar spray of Penshibao (100 ppm) and spraying at 20 and 30 DAT were superior to other treatments. Among the interactions, the treatment combination of soaking seeds in Penshibao + Azospirillum followed by foliar application of Penshibao at 20 and 30 DAT, recorded the highest BCR.